NUT carcinoma of the head and neck: A case report and literature review - Yue Zhao; Jun Zhang; Wenjun Liao; Jiayu Li; Shichuan Zhang (Precision Radiation Oncology)
Abstract Nuclear protein in testis (NUT) carcinoma is a rare and highly aggressive cancer, characterized by rearrangements involving the NUT gene located on chromosome 15q14. In this report, we present the case of a 52‐year‐old female diagnosed with primary parotid NUT carcinoma. Despite undergoing surgery, adjuvant chemotherapy, and incomplete regional radiotherapy, the patient succumbed to the disease after an overall survival duration of 7 months. We retrospectively discuss patient clinical and pathological features, as well as therapeutic approaches of NUT carcinoma of the head and neck.